The Typological Process and the Morphological Period: A Cross-Cultural Assessment. (June 2014) - Whitehand, J W R; Gu, Kai; Conzen, Michael P; Whitehand, Susan M
The concepts 'typological process' and 'morphological period' have received surprisingly little empirical substantiation despite their familiarity to many urban morphologists. They are examined here in two contrasting cultural areas—England and the Shanghai area, China—over the period from the mid-19th century to the late-20th century. Sequences of ordinary residential building types are recognized in the two areas: for example, historical series of terraced house types in England and historical variations on the lilong development unit in the Shanghai area. Periods characterized by different types and connections between those types are identified. The areas are different in both their building types and their periodizations but commonalities in their processes of change, including those related to the spread of Western fashions, are found. The difficulty of uncovering the mechanism of the typological process whereby one form type is succeeded by another reflects major problems of assembling the requisite data. Many more comparative studies, including between contrasting cultural areas, are needed.